Comparative study of the micromorphological and anatomical characteristics of two Artemisia species - Tojić, Teodora (Acta herbologica, 2023)
The genus Artemisia has attracted great interest from plant researchers because of chemical composition and the biological diversity of its species. The aim of this study was to investigate general anatomical features of the vegetative organs of two species of the genus Artemisia (A. vulgaris and A. absinthium) that could be of taxonomic value and potentialy relevant to the production of secondary metabolites. In this study transverse sections of leaves, stems and roots were prepared and microslides were obrerved under the light microscope. The main anatomical difference between these two species is reflected in the presence of trichomes. T-shaped non-glandular trichomes are present on both sides of the leaf epidermis, and on the stem surfaces in both species. However, much fewer glandular trichomes were observed in A. vulgaris than in A. absinthium, which may indicate lower production of secondary metabolites, especially volatiles.